POSITIVE EFFECTS OF AMBIGUITY WHEN CREATED BY RHETORICAL DEVICES: TO BE OR NOT TO BE. - MUZZILLO, JEANNE SMITH (ETC: A Review of General Semantics, 2010)
The article discusses the use of literary ambiguity as a rhetorical device in literature. The to make making certainties elusive for the reader, and the influence of rhetorical devices on the experiences of the reader. Topics include lexical ambiguity and syntactical ambiguity, ambiguity in the works of English playwright William Shakespeare, and the various types of literary devices, including eponym, euphemism, and metonymy.